Development Of Academic Science Karakalpakstan In the Initial Period of Independence (1991-1997) - Seyilbekova Rano Baxit qizi (Zien Journals, 2021)
In 1991, after gaining independence, paying tribute to the national independence of the Republic of Karakalpakstan, the Karakalpak branch of the Academy of Sciences of the Uzbek SSR was transformed into the Karakalpak branch of the Academy of Sciences of the Republic of Uzbekistan. This event raised the authority of the Karakalpak science one step higher. The chairman of the Karakalpak branch of the Academy of Sciences of the Republic of Uzbekistan, academician S.K. Kamalov, was appointed vice-president of the Academy of Sciences of Uzbekistan
Keywords: Karakalpakstan; Academy of Sciences,; Language and Literature